ATIVISA (ACONITUM HETEROPHYLLUM WALL EX. ROYLE): A COMPREHENSIVE REVIEW ON PROPAGATION, TRADITIONAL USES AND PHARMACOLOGY (AYUSHDHARA, 2021)
Aconitum heterophyllum Wall ex. Royle is considered an important medicinal plant in traditional system of medicine as the tuberous roots are used for curing different ailments. But over grazing, prolong seed dormancy and many other reasons have led to the exploitation of this plant, so conservation through various modes is the need of the hour. Aims: The present review aims for accounting extensive information on different methods of propagation, traditional uses and pharmacological activities of Aconitum heterophyllum. Review Methods: A literature search was done on Aconitum heterophyllum using relevant Ayurvedic and contemporary texts. Different scientific databases such as Pubmed, Scopus, EBSCO, Google Scholar Information were used to collect all information regarding propagation and pharmacology of this plant. Results: Available data has reported that this endangered plant can be propagated through various methods such as raising propagules from seeds and daughter tubers, and other plant tissue culture techniques. Plant has reported to have 0.79% of total alkaloids in roots, out of which Atisine (0.4%), Heteratisine (0.3%), histisine, heterophyllisine, heterophylline, heterophyllidine are some major alkaloids. It also possesses important pharmacological activities like anti-bacterial activity, anti-diarrhoeal activity, enzyme-inhibition activity, anti-inflammatory activity, hepato-protective activity and anti-spasmodic activity. Conclusion: The results of this review clearly suggests about the valuable traditional use of Aconitum heterophyllum in curing various ailments like diarrhoea, dysentery, bilious complaints, intermittent fever and diseases of children. Further research: Different traditional uses mentioned in Āyurveda texts need further validation through different experimental and clinical studies which is a recommendation of this review.